2017
DOI: 10.15766/mep_2374-8265.10647
|View full text |Cite
|
Sign up to set email alerts
|

An Experiential Resident Module for Understanding Social Determinants of Health at an Academic Safety-Net Hospital

Abstract: Introduction: Half of the U.S. population has chronic illness. Many disparities exist in health care for management of chronic disease among poorer individuals, including decreased access to healthy foods, homelessness, and difficulty navigating large hospital systems due to low health literacy. A survey of resident physicians found significant gaps in preparedness to provide cross-cultural care. Education is needed to promote consideration of patients' social and cultural barriers in managing disease and navi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Structural competency builds upon existing social determinants of health, cultural competency, and cultural humility curricular efforts. 1,4,5,[22][23][24][25][26][27] In contrast to many curricula framed in terms of the social determinants of health that describe the existence of, but not the historical and contemporary drivers of, health disparities, structural competency situates these social determinants within a broader structural context. For example, a structural competency approach not only characterizes the epidemiology of racial health disparities-it examines the structures that have created and sustain racial inequity (i.e., structural racism).…”
Section: Introductionmentioning
confidence: 99%
“…Structural competency builds upon existing social determinants of health, cultural competency, and cultural humility curricular efforts. 1,4,5,[22][23][24][25][26][27] In contrast to many curricula framed in terms of the social determinants of health that describe the existence of, but not the historical and contemporary drivers of, health disparities, structural competency situates these social determinants within a broader structural context. For example, a structural competency approach not only characterizes the epidemiology of racial health disparities-it examines the structures that have created and sustain racial inequity (i.e., structural racism).…”
Section: Introductionmentioning
confidence: 99%
“…Residents found our curriculum useful for learning about community resources and practicing clinically-oriented conversations related to SDoH as has been described previously [ 7 , 9 , 34 ]. Klein et al also reported trainees experiencing impactful realizations about family circumstances, reflecting about self-perceptions and practices, and gaining knowledge regarding community-based resources after a two-week curriculum combining didactics and immersive experiences involving poverty and provision of health care to underserved populations [ 9 ].…”
Section: Discussionmentioning
confidence: 94%
“…Historically, pediatric trainees have inadequate training to identify and intervene on the unmet needs associated with SDoH [ 6 ]. Recent educational interventions focused on improving the knowledge of and attitudes towards addressing SDoH in a clinical setting have shown promising results [ 7 , 8 ]. Didactic- and immersion-based efforts to provide training to pediatric residents on SDoH have resulted in improved trainee knowledge and comfort with discussing social determinants of health [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…28 Carefully designed curriculum has been developed in other specialties to promote conversation related to racism and health disparities on the wards and in didactics. 29,30 The unique ED environment may require the development of brief tools to aid residency programs in debriefing common difficult patient interactions and prompt provider reflection on personal identity differences, especially in lowresource settings.…”
Section: Training Influences Clinical Preparation and Willingness To Work In Underserved Areasmentioning
confidence: 99%